A Sandwich-Type Electrochemical Immunosensor based on Pd Nanocubes Functionalized MoO2 Nanospheres for Highly Sensitive Detection of CEA. Issue 16 (4th January 2021) - Yang, Qingshan; Wang, Ping; Zhou, Kaiwei; Tang, Chunyuan; Ren, Jie; Li, Yueyun; Liu, Qing; Dong, Yunhui
Abstract : In this study, a sandwich-type electrochemical immunosensor was developed for detecting carcinoembryonic antigen (CEA) effectively. The proposed electrochemical immunosensor was based on gold nanocrystals (Au NDs) as the substrate material for capturing primary antibodies and using palladium nanoscale cubics (Pd NCs) loaded on amino-functionalized MoO2 nanospheres (Pd NCs/NH2 -MoO2 NSs) as a secondary antibody label. Au NDs had dendritic structures that were more conducive to capturing Ab1 and can accelerate electron transfer. MoO2 had the good catalytic capacity for reduction of H2 O2 and favourable electrical conductivity. Similarly, Pd NCs had excellent catalytic performance for hydrogen peroxide reduction. Hence, the obtained Pd NCs/NH2 -MoO2 NSs were more effective than Pd NCs and NH2 -MoO2 NSs in catalytic reduction of hydrogen attribute to a synergistic effect, showing excellent catalysis. The proposed electrochemical immunosensor had a lower detection limit of 3.3 fg ml −1 jand a wider detection range from 10 fg ml −1 to 100 ng ml −1 (S/N = 3) for the detection of CEA under optimal experimental conditions. The proposed electrochemical immunosensor showed good sensitivity, stability, selectivity, reproducibility and its good detection performance of the immunosensor indicated that it had a broad application prospect in clinical detection.